Exploring the Concept, Implications, and Business Potential of Halal Products and Services (Journal of Management and Social Sciences, 2025)
The interest in the halal industry has witnessed a surge in recent times, with practitioners, including entrepreneurs, academics, and policymakers, now exploring halal markets for economic expansion. This development has triggered a new trend in Islamic economic scholarship with massive studies on the halal sector. Given the above, there is a growing need to elucidate the concept, principles, and market opportunities in the halal sector to enhance stakeholders' understanding of the sector. There is a dearth of studies in this area of knowledge, particularly innovative services in the halal sector. This paper, therefore, attempts to explain the concept, principles, and market opportunities in the halal sector to establish the implications on entrepreneurship and business growth. Through a qualitative approach, the paper uses secondary data sourced from peer-reviewed journals to explain products and innovative services in the halal market. The article identifies key factors driving consumer preferences and presents strategic recommendations for businesses seeking to enter or enhance their presence in the halal market. Ultimately, this research aims to provide valuable insights into the burgeoning halal economy and its significance for both local and international markets.KeywordsHalal products, entrepreneurship, Islamic economics, innovative services, Shari’ah